Generating multiple contrasts using single-shot radial T1 sensitive and insensitive steady-state imaging - Benkert, Thomas; Bartsch, Andreas J.; Blaimer, Martin; Jakob, Peter Michael; Breuer, Felix A. (Magnetic resonance in medicine, 2015)
Purpose Recently, the (Resolution Enhanced-) T1 insensitive steady-state imaging (TOSSI) approach has been proposed for the fast acquisition of T2-weighted images. This has been achieved by balanced steady-state free precession (bSSFP) imaging between unequally spaced inversion pulses. The purpose of this work is to present an extension of this technique, considerably increasing both the efficiency and possibilities of TOSSI. Theory and Methods A radial trajectory in combination with an appropriate view-sharing reconstruction is used. Because each projection traverses the contrast defining k-space center, several different contrasts can be extracted from a single-shot measurement. These contrasts include various T2-weightings and T2/T1-weighting if an even number of inversion pulses is used, while an odd number allow the generation of several images with predefined tissue types cancelled. Results The approach is validated for brain and abdominal imaging at 3.0 Tesla. Results are compared with RE-TOSSI, bSSFP, and turbo spin-echo images and are shown to provide similar contrasts in a fraction of scan time. Furthermore, the potential utility of the approach is illustrated by images obtained from a brain tumor patient. Conclusion Radial T1 sensitive and insensitive steady-state imaging is able to generate multiple contrasts out of one single-shot measurement in a short scan time. Magn Reson Med 73:2129-2141, 2015. © 2014 Wiley Periodicals, Inc.